1981
DOI: 10.1083/jcb.90.2.380
|View full text |Cite
|
Sign up to set email alerts
|

Structure of nuclear ribonucleoprotein: identification of proteins in contact with poly(A)+ heterogeneous nuclear RNA in living HeLa cells.

Abstract: The processing of heterogeneous nuclear RNA into messenger RNA takes place in special nuclear ribonucleoprotein particles known as hnRNP. We report here the identification of proteins tightly complexed with poly(A) + hnRNA in intact HeLa cells, as revealed by a novel in situ RNA-protein cross-linking technique. The set of cross-linked proteins includes the A, B, and C "core" hnRNP proteins, as well as the >42,000 mol wt species previously identified in noncross-linked hnRNP. These proteins are shown to be cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 49 publications
1
47
0
Order By: Relevance
“…10C) (5 ,ug/ml for 2 h); T, total cell material; P, polyribosomal fraction after selection on an oligo(dT)-cellulose-_ column as detailed in the legend to Fig. 8. the ability of UV light to generate photoreactive species of RNA and thus bring about cross-linking of mRNA to pro--teins which are in direct contact with it in the intact cell (10,34,35,50,51,53 (39,42) and in vitro (29) have also been described. The relationship between these observations and the altered interaction of 38K with mRNA is not known, but it may be that 38K is involved in mRNA stabilization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10C) (5 ,ug/ml for 2 h); T, total cell material; P, polyribosomal fraction after selection on an oligo(dT)-cellulose-_ column as detailed in the legend to Fig. 8. the ability of UV light to generate photoreactive species of RNA and thus bring about cross-linking of mRNA to pro--teins which are in direct contact with it in the intact cell (10,34,35,50,51,53 (39,42) and in vitro (29) have also been described. The relationship between these observations and the altered interaction of 38K with mRNA is not known, but it may be that 38K is involved in mRNA stabilization.…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the fact that nonspecific interactions between RNA and proteins are likely to occur in vitro (2,14,38). UV cross-linking of RNA to protein in intact cells overcomes these difficulties and allows the identification of proteins which are in direct contact with hnRNA and mRNA in vivo (10,34,35,50,51,53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A more stringent definition of genuine hnRNP proteins has been provided by UV light-induced covalent cross-linking of proteins to RNA in vivo, which allows identification of proteins that are bound to the RNA in the cell (Mayrand et al 1981;Dreyfuss et al 1984a, b). These studies showed numerous proteins, including those that correspond in SDS-PAGE mobility to A, B, and C proteins, but the proteins are no longer useful for biochemical studies.…”
Section: ; Vanmentioning
confidence: 99%
“…The first described spliceosome proteins were called hnRNP proteins, based on their association with large heterogeneous nuclear RNA transcripts now known to include unspliced pre-mRNAs (6)(7)(8)(9)(10)(11)(12). The C-group hnRNP proteins are abundant nuclear proteins of Mr 42,000-44,000 that have been implicated in splicing (13,14) and are known to be phosphorylated in vivo (8,(15)(16)(17) by a casein kinase II-type activity (18,19).…”
mentioning
confidence: 99%